Credit attitude, money attitude and credit misuse among university students in China - Kao, Wen Tao; Lau, Jasmine Leby (Malaysia Consumer And Family Economy Association (MACFEA), 2022)
The purpose of this paper is to investigate the relationship between credit and money attitudes with credit misuse among university students in Sichuan, China. A sample of 150 undergraduate students was collected from Sichuan University, the University of Electronic Science and Technology, and the Southwestern University of Finance and Economics. Descriptive analysis and Pearson correlation coefficient were used to analyze the data. Pearson correlation analyses found that affective, cognitive, and behavioral credit attitudes had no significant relationship with credit misuse. On the other hand, the five components of money attitude namely achievement and success, saving concerns, mindfulness and responsible, power and status as well as financial literacy worries had a significant positive relationship with credit misuse. This study provided relevant information to relevant parties to prevent credit misuse from becoming widespread among university students.